2017
DOI: 10.1161/jaha.116.005340
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Arrhythmias and Electroanatomical Remodeling in Patients With Left Ventricular Assist Devices

Abstract: BackgroundThe incidence, predictors, and impact of atrial arrhythmias along with left atrial structural changes in patients with left ventricular assist devices (LVADs) remain undetermined.Methods and ResultsAll patients who underwent LVAD implantation from 2008 to 2015 at the University of Chicago Medical Center were included. Electronic medical records, electrocardiograms, echocardiograms, and cardiac electrical device interrogations were reviewed. The association of arrhythmias and clinical covariates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 37 publications
(77 reference statements)
3
52
0
Order By: Relevance
“…It also demonstrated a strong trend toward increased mortality rate, though it did not reach statistical significance. The study by Deshmukh et al reported a similar finding and further categorized patients into a paroxysmal AF group and permanent/persistent AF group. This study noted that a history of persistent/permanent AF was an independent predictor of mortality, while the group with a history of paroxysmal AF was not associated with an increased death rate.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…It also demonstrated a strong trend toward increased mortality rate, though it did not reach statistical significance. The study by Deshmukh et al reported a similar finding and further categorized patients into a paroxysmal AF group and permanent/persistent AF group. This study noted that a history of persistent/permanent AF was an independent predictor of mortality, while the group with a history of paroxysmal AF was not associated with an increased death rate.…”
Section: Discussionmentioning
confidence: 61%
“…Almost every patient in the pooled analysis had continuous flow devices. Less than 2% of patients in the study of Deshmukh et al used pulsatile LVADs. A summary of the included studies and clinical characteristics are provided in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations